Virtual Reality for Vestibular Rehabilitation: A Systematic Review. Issue 7 (August 2021) - Xie, Michael; Zhou, Kelvin; Patro, Nivedh; Chan, Teffran; Levin, Marc; Gupta, Michael K.; Archibald, Jason
Abstract : Introduction: Vertigo is a debilitating symptom, leading to increased healthcare utilization and lost patient productivity. Vestibular rehabilitation is used to manage the symptomatic manifestations of vestibular disease. However, vestibular rehabilitation is limited by accessibility and time commitment. Recently, virtual reality has been described as a vestibular rehabilitation tool that may circumvent these barriers to treatment. Despite this, the efficacy of virtual reality for vestibular rehabilitation remains unclear. This study aims to review and summarize the current literature on the effectiveness of virtual reality-based vestibular rehabilitation. Methods: A systematic review of the MEDLINE, EMBASE, and Alternative and Complementary Medicine databases was conducted for prospective studies describing virtual reality-based vestibular rehabilitation. Results: Our search identified 382 unique articles. Six randomized controlled trials and four other studies were ultimately included. Study sample sizes ranged from 13 to 70 participants and varied in diagnoses from any unilateral peripheral vertigo to specific pathologies. Different virtual reality interventions were used. Comparator groups ranged from supervised vestibular rehabilitation to independent Cawthorne-Cooksey exercises. Outcomes consisted of validated questionnaires, objective clinical tests, and measurements of balance or reflexes. Conclusion: The studies reviewed in this study are preliminary evidence to suggest the benefit of virtual reality-based vestibular rehabilitation. However, these studies are limited by their inclusion criteria, heterogeneity, comparator design, and evidence-based clinical outcomes. Further research should address these limitations.